2004
DOI: 10.1063/1.1790072
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced metastability in hydrogenated nanocrystalline silicon solar cells

Abstract: Light-induced metastability in hydrogenated nanocrystalline silicon (nc-Si:H) single-junction solar cells has been studied under different light spectra. The nc-Si:H studied contains a certain fraction of hydrogenated amorphous silicon (a-Si:H). We observe no light-induced degradation when the photon energy used is lower than the bandgap of a-Si:H, while degradation occurs when the photon energy is higher than the bandgap. We conclude that the light-induced defect generation occurs mainly in the amorphous phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 8 publications
5
48
1
Order By: Relevance
“…Previous works demonstrated that some c-Si: H solar cells present a milder form of light-induced degradation, depending on the crystalline volume fraction. [12][13][14][15][16][17][18][19] Klein et al 12 reported a relative decrease of the conversion efficiency of up to 10% after 1000 h of degradation for highly amorphous c-Si: H solar cells; we confirmed, by studying dilution series of c-Si: H solar cells, that the higher the crystallinity, the lower the relative drop in efficiency. 13 Yan et al investigated the influence of the illumination spectra on the lightinduced degradation, 14 as well as the influence of the electrical bias.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Previous works demonstrated that some c-Si: H solar cells present a milder form of light-induced degradation, depending on the crystalline volume fraction. [12][13][14][15][16][17][18][19] Klein et al 12 reported a relative decrease of the conversion efficiency of up to 10% after 1000 h of degradation for highly amorphous c-Si: H solar cells; we confirmed, by studying dilution series of c-Si: H solar cells, that the higher the crystallinity, the lower the relative drop in efficiency. 13 Yan et al investigated the influence of the illumination spectra on the lightinduced degradation, 14 as well as the influence of the electrical bias.…”
Section: Introductionsupporting
confidence: 67%
“…[12][13][14][15][16][17][18][19] Klein et al 12 reported a relative decrease of the conversion efficiency of up to 10% after 1000 h of degradation for highly amorphous c-Si: H solar cells; we confirmed, by studying dilution series of c-Si: H solar cells, that the higher the crystallinity, the lower the relative drop in efficiency. 13 Yan et al investigated the influence of the illumination spectra on the lightinduced degradation, 14 as well as the influence of the electrical bias. 15 They initially concluded that the amorphous phase was solely responsible for the light-induced degradation observed in c-Si: H. Nevertheless, they lately suggested that small grains and/or intermediate-range order could as well play an important role regarding the stability of c-Si: H solar cells.…”
Section: Introductionsupporting
confidence: 67%
“…In spite of the immense potential of high efficiencies and large area deposition capabilities shown by µc-Si:H in semiconductor technology, especially in photovoltaics 24,25 and TFTs, 26 the understanding of its transport properties is impeded by these lacunae. Different conduction mechanisms and paths have been invoked to explain the electrical transport behavior in µc-Si:H, deriving information that correlate only some microstructural features and mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the passivation properties of amorphous tissue which surround the grain boundaries. But an increased amorphous concentration in the intrinsic layer leads to degradation in the electronic properties of the device, under prolonged light exposure [133,134,135,136].…”
Section: Light Soaking Propertiesmentioning
confidence: 99%